Diversity And Inclusion In The Workplace Of Civil Engineering Firms In South Africa - Ramone, Ntsitile (University of the Witwatersrand, Johannesburg, 2021)
The narrative of engineering as a masculine profession has replicated the observation that engineering is incongruous for women. Although efforts to encourage females to get into the engineering field have been made, a number of them have failed. At the same time, it has been argued that the way gender is ‘done’ in work can help diminish or increase inequality between the sexes. Diversity symbolises the synchronicity of employees with an extensive variation of socio-cultural, socio-economic as well as demographic characteristics. Inclusion designates the optimal employment of a blended workforce for the development and success of an organisation by providing a sense of connection, empowerment, acknowledgement, respect to the diverse workforce as well as integration. Gender inequality can also be viewed as the cultural and social situation in which gender determines different rights and self-worth for women and men, which are echoed in their imbalanced access to rights, as well as the hypothesis of pigeonholed social and cultural roles Using case study research exploring diversity and inclusion in the workplace of South African civil engineering firms in Gauteng, this study aims to explore the relationship between diversity and inclusion attributes such as gender inequality, pay disparities, gender based discrimination, skills as well as unfavourable work conditions and how they affect job performance and in turn inhibit growth in the industry. A case study approach was used through conducting semi-structured interviews that enabled in-depth insights from participants to get a thorough understanding of the concepts under review
A research report presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg 2021
Keywords: DIVERSITY; INCLUSION; GENDER INEQUALITY; UCTD; SDG-5: Gender equality